Scientific Basis for the Selection of Promising and New Mulberry Varieties on the Territory and in the Conditions of the Republic of Karakalpakstan. (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents the scientific basis of breeding mulberry varieties in the conditions of Karakalpakstan. Based on the results of the analysis, the economic effect of the methods of breeding mulberry varieties is determined.